Endoscopic bariatric therapies for treating obesity: a learning curve for gastroenterologists - Shahnazarian, Vahe; Ramai, Daryl; Sarkar, Avik (Translational Gastroenterology and Hepatology, 2019)
Obesity represents a growing public health threat. Until recently, surgery was the primary means for treating pharmacotherapy resistant obese patients. However, therapeutic endoscopy has evolved as an effective and safe alternative strategy. Particularly, endoscopic bariatric therapy (EBT) can bridge the gap in patients who do not fit the BMI criteria for surgery and fail conservative or medical therapy. Today there are many tools within the realm of EBT available to endoscopists. While there are no formal guidelines for their use, training and use of these tools are limited by the type of institution, preferences of senior endoscopists, cost, and availability. We review different EBT tools available to trainees and gastroenterologist, and the learning curves associated with them.